Oral Labetalol in Comparison with Methyldopa in Treatment of Gestational Hypertension as a First Line Drug - Tasneem Akhter, Khiaynat Sarwar Hashmi, Saba Kaynat, Sarwat Faridi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Defining hypertension in pregnancy, it is taken as systolic blood pressure of 140 or more and diastolic blood pressure of 90mg or more. Presence of proteinurea differentiates chronic hypertension and gestational hypertension from pre eclampsia .Prevalence and incidence of hypertension in pregnancy along with its complications like end-organ damage, preeclampsia, eclampsia, and postpartum eclampsia are increasing. Gestational hypertension and its sequels are major causes of fetal and maternal morbidity and mortality and affect almost 8% of pregnancies. Labetalol and methyldopa were effective in reducing systolic and diastolic BP significantly but labetalol was found to control BP more rapidly and efficiently. Safety profile of both drugs was similar. The rationale of this study is Labetalol is more effective in comparison with Methyldopa in pregnancy induced hypertensive females in terms of control of blood pressure within 48hours of drug intake, in pregnant patients between POG of 28 to 32 weeks. Design: Randomized control trial. Place and Duration of Study: Department of Gynaecology Unit 2 Bahawal Victoria Hospital, Bahawalpur from 1st January 2022 to 31st December 2022. Methodology: One hundred 100 patients having gestational hypertension between periods of gestation from 28to 32 weeks were enrolled. They were divided into 2 groups; group A treated with labetalol and B treated with methyldopa respectively. Results: Statistical no significant difference in systolic and diastolic blood pressure was observed before starting treatment in both groups but a significant fall in diastolic blood pressure was observed in group A after 48 hrs of initiation of treatment i.e., with labetalol (P = 0.007) Conclusion: Both labetalol and methyldopa reduce blood pressure in women with gestational hypertension but labetalol is more effective than methyldopa as proved by our study. Keywords: Gestational hypertension, Diastolic blood pressure, Labetalol, Methyldopa